IMPLEMENTASI AKUNTANSI PADA SISTEM PENGGAJIAN DAN BONUS KARYAWAN PT MONDELEZ INTERNATIONAL - Novita Setianti; Riana Safitri; Lucky Giovanni; Susi Apriana (Universitas Dian Nuswantoro, 2023)
The payroll process at Mondelez International Incorporated Company is currently using Microsoft Excel. Employee attendance data is obtained from https://front-mdlz.com/. The treatment process is error-prone, so time is wasted to revise again when an error occurs. In addition, payroll data for each period is also not centered in the database because the excel file used only stores payroll data per period. In this study an application was made that can easily calculate the salary and bonus of PT Mondelez International employees.The research uses prototyping method as a system development method. this application has been tested for the performance based on the Dimension Quality for Goods and can facilitate the payroll and employee bonuses. This results of product testing were carried out by 10 people. From the 2 tests, the highest product test value was 90,4. With a limit on the value of the product ?75, the product is declared successful. The results of testing the benefits carried out by 10 respondents and obtained an average value of ULEA is 95% where usability aspects 93%, learnability 97%, efficiency 97% and acceptability 80%. With a product success value limit of product 75%, the product is declared beneficial.